2023
DOI: 10.1177/20427530231180029
|View full text |Cite
|
Sign up to set email alerts
|

Afghan undergraduate students’ perceptions toward e-learning

Abstract: E-learning provides teachers and students with great opportunities and benefits, by enhancing teaching and learning experiences. Although e-learning is widely adopted in educational systems, some countries still use traditional teaching methods with limited use of technology as a medium of teaching and learning. This study investigates the perceptions of Afghan EFL undergraduate students toward e-learning at a public university in Afghanistan. Few studies have investigated the use of e-learning in tertiary-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 92 publications
1
6
0
Order By: Relevance
“…These findings parallel Thapa et al (2021), who reported that the main benefit of e-learning for nursing students was the opportunity to stay at home. This finding is also similar to the results of Monib (2023), who found that undergraduate students perceive elearning as useful in higher education.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These findings parallel Thapa et al (2021), who reported that the main benefit of e-learning for nursing students was the opportunity to stay at home. This finding is also similar to the results of Monib (2023), who found that undergraduate students perceive elearning as useful in higher education.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the study by Bali and Liu (2018) demonstrated that traditional classroom instruction received higher ratings regarding social presence, interaction, and overall satisfaction than online learning. On the other hand, According to Monib (2023), over 50.0% of participants favored hybrid learning that combines online and faceto-face instruction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations